2020
DOI: 10.1542/peds.2019-0306
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Albuterol Use in Children With Bronchiolitis

Abstract: OBJECTIVES:In 2014, the American Academy of Pediatrics published bronchiolitis guidelines recommending against the use of bronchodilators. For the winter of 2015 to 2016, we aimed to reduce the proportion of emergency department patients with bronchiolitis receiving albuterol from 43% (previous winter rate) to ,35% and from 18% (previous winter rate) to ,10% in the inpatient setting.METHODS: A team identified key drivers of albuterol use and potential interventions. We implemented changes to our pathway and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…A 2014 systematic review 18 of 14 published QI initiatives in inpatient bronchiolitis care found that these interventions were associated with reductions in bronchodilator, steroid, antibiotic, and CR use. The QI efforts included in this review or published after the review have been associated with reduced use of nonrecommended services by implementing local clinical pathways citing AAP recommendations [19][20][21][22][23][24][25][26][27][28][29] ; international studies using other national guidelines as the basis for local improvements have been associated with similar improvements. [30][31][32][33] Such QI efforts constitute 1…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%
“…A 2014 systematic review 18 of 14 published QI initiatives in inpatient bronchiolitis care found that these interventions were associated with reductions in bronchodilator, steroid, antibiotic, and CR use. The QI efforts included in this review or published after the review have been associated with reduced use of nonrecommended services by implementing local clinical pathways citing AAP recommendations [19][20][21][22][23][24][25][26][27][28][29] ; international studies using other national guidelines as the basis for local improvements have been associated with similar improvements. [30][31][32][33] Such QI efforts constitute 1…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%
“…In another large teaching hospital, a multidisciplinary group updated the in‐house bronchiolitis treatment guidelines for the 2015–2016 season 20 . In addition, salbutamol use was automatically monitored, and the clinicians received weekly updates.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies from the USA reported rather good results when the AAP 2006 and 2014 guidelines were implemented, and followed up, by multi-professional teams. [19][20][21][22] In one large teaching hospital, a multidisciplinary team developed and implemented the clinical practice guidelines for managing childhood bronchiolitis before the 2011 season. 19 This involved teamwork, collaboration, joint education, providing online access to the guidelines, data sharing and monthly team meetings.…”
Section: Impact Of Guidelines Plus Interventionsmentioning
confidence: 99%
“…A single study evaluating the effects of epinephrine, levalbuterol, and racemic albuterol/salbutamol in mechanically ventilated children with bronchiolitis found a statistically significant, but clinically futile effect on airway peak pressures [47]. As such, the AAP advises against the use of bronchodilators for viral bronchiolitis [31] and a recent clinical study reporting no negatively affected clinical outcome after decreased use of albuterol affirms this recommendation [48].…”
Section: Viral Bronchiolitismentioning
confidence: 99%